Exogenous induction of the iron dicitrate transport system of Escherichia coli K-12. - Zimmermann, L (1984)
Streptonigrin was used to select mutants impaired in the citrate-dependent iron transport system of Escherichia coli K-12. Mutants in fecA and fecB could not transport iron via citrate. fecA-lac and fecB-lac operon fusions were constructed with the aid of phage Mu dl(Ap lac). Strains deficient in ferric dicitrate transport which were mutated in fecB were as inducible as transport-active strains. They expressed the FecA outer membrane protein and beta-galactosidase of the fecB-lac operon fusions. In contrast, all fecA::lac mutants and fecA mutants induced with N-methyl-N'-nitro-N-nitrosoguanidine did not respond to ferric dicitrate supplied in the growth medium. tonB fecB mutants which were lacking all tonB-related functions were not inducible. We conclude that binding of iron in the presence of citrate to the outer membrane receptor protein is required for induction of the transport system. In addition, the tonB gene has to be active. However, iron and citrate must not be transported into the cytoplasm for the induction process. These data support our previous conclusion of an exogenous induction mechanism. Mutants in fur expressed the transport system nearly constitutively. In wild-type cells limiting the iron concentration in the medium enhanced the expression of the transport system. Thus, the citrate-dependent iron transport system shares regulatory devices with the other iron transport systems in E. coli and, in addition, requires ferric dicitrate for induction.